2016
DOI: 10.1177/0891988716673466
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Vitamin B Supplementation on Cognition in Elderly Patients With Cognitive-Related Diseases

Abstract: Increase in serum homocysteine is shown to be a potential risk factor for cognitive impairment. Evidence suggests that vitamin B supplementation may reduce cognitive decline by lowering the homocysteine levels. The current meta-analysis evaluated the efficacy of folic acid along with vitamin B12 and/or B6 in lowering homocysteine, thereby attenuating cognitive decline in elderly patients with Alzheimer disease or dementia. Randomized controlled trials (RCTs) comparing the efficacy of folate and B vitamin suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 39 publications
(94 reference statements)
0
57
0
3
Order By: Relevance
“…In the last decade, various research studies worldwide have reported low levels or deficiency in vitamin B 12 among the studied populations [13,14,15]. As a consequence, B 12 supplementation has been recommended in many occasions as a key contribution to the maintenance and enhancement of population health [13,15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, various research studies worldwide have reported low levels or deficiency in vitamin B 12 among the studied populations [13,14,15]. As a consequence, B 12 supplementation has been recommended in many occasions as a key contribution to the maintenance and enhancement of population health [13,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, B 12 supplementation has been recommended in many occasions as a key contribution to the maintenance and enhancement of population health [13,15,16]. Vitamin B 12 deficiency was found to be multifactorial, and most of time it was related to malabsorption, malnutrition, or drug induced causes [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Second, there was a significant difference in the age between suicide attempters and non-attempters. Many studies have found that the common factors which may exacerbate folate deficiency are (2020) 10:5008 | https://doi.org/10.1038/s41598-020-57411-1 www.nature.com/scientificreports www.nature.com/scientificreports/ older age, male sex, and alcoholism [61][62][63] . Third, there were more female subjects in the SCZ group, which may have led to bias in the statistical analysis due to the imbalance in the number of subjects in each sex category in our current study.…”
Section: Discussionmentioning
confidence: 99%
“…The B vitamins appeared to lower the subjects' homocysteine levels, resulting in reduced gray matter atrophy and slower cognitive decline [24]. However, a metaanalysis by Zhang and colleagues found that while intervention groups treated with vitamins B6, B12, and folate often experienced a reduction in homocysteine levels, these reductions were not translated into better cognition [25]. As demonstrated by these two studies, the effects of the B vitamins on cognition are uncertain.…”
Section: Vitamin Bmentioning
confidence: 99%